A Hypothesis of the Co-evolution of Cooperation and Responses to Inequity - Brosnan, Sarah F. (Frontiers in Neuroscience, 2011)
Recent evidence demonstrates that humans are not the only species to respond negatively to inequitable outcomes which are to their disadvantage. Several species respond negatively if they subsequently receive a less good reward than a social partner for completing the same task. While these studies suggest that the negative response to inequity is not a uniquely human behavior, they do not provide a functional explanation for the emergence of these responses due to similar characteristics among these species. Emerging data support the hypothesis that an aversion to inequity is a mechanism to promote successful long-term cooperative relationships amongst non-kin. In this paper, I discuss several converging lines of evidence which illustrate the need to further evaluate this relationship. First, cooperation can survive modest inequity; in explicitly cooperative interactions, individuals are willing to continue to cooperate despite inequitable outcomes as long as the partner’s overall behavior is equitable. Second, the context of inequity affects reactions to it in ways which support the idea that joint efforts lead to an expectation of joint payoffs. Finally, comparative studies indicate a link between the degree and extent of cooperation between unrelated individuals in a species and that species’ response to inequitable outcomes. This latter line of evidence indicates that this behavior evolved in conjunction with cooperation and may represent an adaptation to increase the payoffs associated with cooperative interactions. Together these data inform a testable working hypothesis for understanding decision-making in the context of inequity and provide a new, comparative framework for evaluating decision-making behavior.